PERAN MAHKAMAH KONSTITUSI DALAM PENGUATAN DEMOKRASI KONSTITUSIONAL - Thaher, Irmanjaya (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
The Constitutional Court is a strategic state institution that serves as the guardian of the supremacy of the constitution and the protector of citizens’ constitutional rights. This institution reflects a commitment to the principle of constitutionalism in limiting state power through democratic institutional mechanisms. This study analyzes the Constitutional Court’s role in strengthening Indonesia’s constitutional democracy through four dimensions: its function as guardian of the supremacy of the constitution, its role in democratization and electoral disputes, threats to the institution’s independence, and its institutional design based on international comparative standards to formulate recommendations for strategic strengthening. The research methodology employed a Systematic Literature Review (SLR) conducted systematically, transparently, and structured to identify, evaluate, and synthesize relevant scientific findings to gain a comprehensive understanding and formulate theoretical and practical implications. The results show that the Constitutional Court performs an irreplaceable function in maintaining the supremacy of the constitution, the balance of power, and the resolution of electoral disputes, strengthening the quality of democracy. However, there are serious threats in the form of political intervention and the paradox of judicial authoritarianism that erode the institution’s independence and integrity, necessitating the strengthening of protection mechanisms and urgent institutional reform. The study concluded that the Constitutional Court’s effectiveness as a guardian of the constitution is largely determined by the consistency of its enforcement of judicial review, integrity in resolving election disputes, protection of its independence from political interference, and appropriate institutional design. Improvements based on international comparative standards are a strategic step to optimize the Constitutional Court’s contribution to realizing a stable and sustainable constitutional democracy in Indonesia.